Correlation between Nutritional Status (According to Body Weight/Body Height Index) with the Age of Menarche on Female Student - Dwi Prasetyaningati; Agustina Maunaturohmah (Babali Nursing Research, 2021)
Introduction: Changes that happened in the adolescent population marks by puberty and complex emotional change, social adaptation to be more mature, and sexual identity development to reach the reproductive organ maturation. Methods: This study employed a survey method with the cross-sectional approach. The study population was 28 third-year female students at Sidorejo Pare Christian School. From the total population, twenty-five participants in this study selected by a purposive sampling technique. Two variables, independent variable (nutritional status), dependent variables (the age of menarche), and control variable (social-economic status, health, consumption of medication, and psychological status) involved in this study. Results: Ninety-two percent of the participants had a normal nutritional status. While the rest four percent of them had an underweight nutritional status. The highest percentage of the age of menarche was 11 years old. While the youngest and the oldest age of menarche were 9 and 13, respectively. Ninety-two percent of the participants were experiencing menarche at the age of 9-11 years old, while eight percent of the participants were experiencing menarche at the age of 12 and 14. Conclusion: The oldest and youngest age of menarche found was 11 and 9 years old, respectively. Ninety-two percent of the participant with good nutritional status were experiencing menarche at the age of 9-11. There was a correlation between the nutritional status (according to the index of body weight/body height) with the age of menarche.